Emodin suppresses migration and invasion through the modulation of CXCR4 expression in an orthotopic model of human hepatocellular carcinoma - Manu, K.; Shanmugam, M.; Ong, T.; Subramahniam, A.; Siveen, K.; Perumal, E.; Samy, R.; Bist, P.; Lim, L.; Kumar, Alan Prem; Hui, K.; Sethi, G. (Public Library of Science, 2013)
Accumulating evidence(s) indicate that CXCL12-CXCR4 signaling cascade plays an important role in the process of invasion and metastasis that accounts for more than 80% of deaths in hepatocellular carcinoma (HCC) patients. Thus, identification of novel agents that can downregulate CXCR4 expression and its associated functions have a great potential in the treatment of metastatic HCC. In the present report, we investigated an anthraquinone derivative, emodin for its ability to affect CXCR4 expression as well as function in HCC cells. We observed that emodin downregulated the expression of CXCR4 in a dose-and time-dependent manner in HCC cells. Treatment with pharmacological proteasome and lysosomal inhibitors did not have substantial effect on emodin-induced decrease in CXCR4 expression. When investigated for the molecular mechanism(s), it was observed that the suppression of CXCR4 expression was due to downregulation of mRNA expression, inhibition of NF-κB activation, and abrogation of chromatin immunoprecipitation activity. Inhibition of CXCR4 expression by emodin further correlated with the suppression of CXCL12-induced migration and invasion in HCC cell lines. In addition, emodin treatment significantly suppressed metastasis to the lungs in an orthotopic HCC mice model and CXCR4 expression in tumor tissues. Overall, our results show that emodin exerts its anti-metastatic effect through the downregulation of CXCR4 expression and thus has the potential for the treatment of HCC.